Conservation Status of Virginia Populations of the Rare and Jeopardized Bridle Shiner, Notropis bifrenatus - Wayne C. Starnes; Gabriela M Hogue; Morgan E Raley (Southeastern Fishes Council Proceedings, 2025)
The Bridle Shiner, Notropis bifrenatus (Cope, 1867), Family Leuciscidae, is a small minnow species that ranges in Atlantic coastal river drainages of eastern North America from the St. Lawrence in Canada southward to the Santee River basin of South Carolina. Over several decades notable declines throughout its range have been observed and multiple natural resource agencies note it to be jeopardized with probable extirpations evident in a number of drainages. The Virginia Department of Game and Inland Fisheries recognized the need to assess the status of the Bridle Shiner within its historical range in Virginia. Here we report the results of field surveys and preliminary molecular investigations undertaken to evaluate the species' current distribution and status. Currently, in Virginia, all remaining documented populations are confined to the greater James River basin in the Coastal Plain and lower Piedmont. Based on our findings, recommendations are made for targeted future sampling efforts to enhance detection of small, isolated populations of Bridle Shiner.
Keywords: Bridle Shiner; Notropis bifrenatus; jeopardized; Virginia